Does Our Future Rest in Corporate Hands? Study of Krakow Top Ten Corporate Employers’ Commitment to UN Sustainable Development Goals - Buła, Piotr; Thompson, Anna; Żak, Agnieszka (Czy nasza przyszłość spoczywa w rękach korporacji? Badanie zaangażowania dziesięciu najlepszych pracodawców korporacyjnych w Krakowie w realizację Celów Zrównoważonego Rozwoju ONZ, 2023)
Increasingly, and to a greater extent than in the past, the private sector is taking responsibility to confront global game changers and wicked problems, and act on the UN Sustainable Development Goals (SDGs). This approach offers a huge opportunity to build alliances and work with different sectors, which is one of the key approaches to meeting the challenges of VUCA and realising CSR 4.0. In order to find an answer to the question of whether our future rests in corporate hands, the authors analysed the activities of the 10 largest multinational corporations operating in Krakow in terms of selected CSR 4.0 principles with a particular focus on the implementation of the SDGs. For this purpose, the following research methods were used: literature analysis, content analysis of sustainability reports and comparative analysis. Even within the limited scope of the presented literature review and comparative analysis, this article highlights the enormous potential of the private sector in driving the positive change we need globally, as laid out in the UN Sustainable Development Goals. The private sector has greater resources, is better able to handle risk and innovate, it stands to be not just a key partner, but potentially the key agent of change, in particular in the face of mounting global game changers and wicked problems.
Buła, P., Thompson, A., and Żak, A. (2023). Does Our Future Rest in Corporate Hands? Study of Krakow Top Ten Corporate Employers’ Commitment to UN Sustainable Development Goals. In M. Hajdas (Ed.), Game Changers in Management (pp. 9-29). Publishing House of Wroclaw University of Economics and Business.
Keywords: CSR 4.0; Sustainable Development Goals; SDGs; cross-sector partnership; game changers; change management; cele zrównoważonego rozwoju; partnerstwa międzysektorowe; zarządzanie zmianą